The impact of foreign direct investment on tourism industry in srilanka - Mustafa, A.M.M. (University of Jaffna, 2014)
Tourism is one of the largely and rapidly growing industries in the world. It has become one of the most significant sectors in many developing countries. Sri Lanka is one of the major tourist attraction destinations in South Asian region. After the economic reforms in 1977, the successive governments have implemented various attractive policies and programmes to promote tourism in pursuing economic growth and development. Moreover, the government has employed a number of initiatives in order to encourage and attract Foreign Direct Investment (FBI) towards the tourism industry. The aim of this study is to investigate the long-run and the short-run relationship between tourism and Foreign Direct Investment in Sri Lanka. Annual data gathered for the period from 1978 to 2011 and forecasted data for the period from 2012 to 2016 were used for the study. Data were analyzed using Minitab and E-Views while preliminary calculations were done using MS Excel. Augmented Dickey- Fuller is used for unit root test, while Engle-Granger is used for co-integration, whereas Granger causality test was employed to find the causal relationships. The empirical evidence shows that there is a statistically significant positive relationship between tourism receipts and Foreign Direct Investment in the long-run and the short run. Granger causality test revealed that there exists two way causality implying that Foreign Direct Investments helped to boost tourism sector while tourism earnings stimulated the Foreign Direct Investment. In addition, this research has identified various problems faced in attracting FDI in the Tourism sector and the appropriate recommendations have been presented in order to realize the major benefits from FDI inflow into the country on tourism industry.
Keywords: Tourism; Foreign direct investment; Economic growth; Co-integration; Casuality